EVALUASI KUAT TEKAN BETON MUTU TINGGI YANG MENGANDUNG TULANGAN SATU ARAH - Rudiansyah Putra; Taufiq Saidi; Muttaqin Hasan; Mahlil Mahlil (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2021)
The concrete compressive strength in existing buildings can be determined by the destructive method (DM) and the non-destructive method (NDM). The non-destructive method can be carried out to determine the distribution of the compressive strength of concrete in structural elements, but the value given is not absolutely representative of the actual compressive strength of the concrete. To find out the actual compressive strength of concrete is to carry out destructive tests such as core drilling oncrete. In general, core concrete is not allowed to have reinforcement, but this is sometimes unavoidable. The purpose of this study was to evaluate the compressive strength of high-strength concrete due to the content of reinforcement in the concrete. This study used a concrete cylindrical specimen with a diameter of 10 cm with a variation of the ratio L/D = 1 and L/D = 2. One reinforcement was placed on 1/4 L and 1/2 L of each specimen horizontally with the number of specimens per variation being 5 specimens. The total number of cylindrical specimens was 30 specimens. In this study, specimens without reinforcement were also made as control specimens. Based on the results, it was found that the value of the reinforcement content factor (C2) was still relevant to be used for the L/D = 2 specimens because it still had a deviation below 5%. Meanwhile, for L/D = 1 multiplication with the value of C2 shows a deviation above 5%. The position of the reinforcement that was getting closer to the half height of the specimens decreases the compressive strength of high-strength concrete.